Approach to estimate travel time using sparsely sampled GPS data in urban networks. Issue 15 (1st July 2013) - Hadachi, A.; Mousset, S.; Bensrhair, A.
Abstract : The aim of this reported work is to estimate travel time on urban road sections. The concerned roads are the ones with no dedicated sensing infrastructure and for which the only potentially available source of data is sparse GPS probe data. Presented is a new approach to solve this problem by using an applied particle filter method and historical probabilities distributions of travel time per road section.